Ophthalmic surgery - Saxena, Sandeep (Anshan gold standard mini atlas series., 2007)
Gathers together a group of experts to address the status of eye surgery. In this title, international contributors deal with eyelid and orbital surgery, corneal and refractive surgery, glaucoma surgery and phacoemulsification, small incision and pediatric cataract surgery, vitro-retinal, macular and strabismus surgery.